The Art of Social Reproduction. (August 2016) - Horne, Victoria
This article considers how the museum produces knowledge about the past and present of feminist politics through its framing of marginal, activist artworks that have engaged the sphere of social reproduction or care labour. It is contended that neoliberalism's assault on social reproduction in our current 'age of austerity' – which sees responsibility displaced from the state onto individuals – has sparked a reengagement with earlier socialist–feminist discourse and, as a result, we are perceptibly enmeshed within a new age of social reproduction debates. The Hackney Flashers' germinal photographic project Who's Holding the Baby? (1976–1978), acquired by Madrid's Reina Sofia in 2010, is taken as a case study to explore a range of contextual, temporal and historical contradictions in further detail. Examining the ambiguous relocation of this photographic project provokes vital questions about the contribution of culture to the troubled terrains of art, property and care labour in the 21st century.